Pedagogical Coordination in Secondary Schools from a Distributed Perspective. Adaptation of the Distributed Leadership Inventory (DLI) in the Spanish Context - Inmaculada García-Martínez; Pedro J. Arrifano Tadeu; José Luis Ubago-Jiménez; Carlos Brigas (MDPI AG, 2020)
Introduction: Leadership as the second factor in school improvement needs potential leaders to be effective. Method: The present study aimed to know the potential capacity of leaders in Spanish secondary schools through the adaptation of the DLI questionnaire to Spanish. To accurately adapt this questionnaire, the present research group conducted content validity processes in 2017, using the Delphi Method, in which eight experts from the Spanish Network for Research into Leadership and Academic Improvement were invited to participate (RILME). As part of a pilot test, preliminary tools were administered to 547 participants from secondary schools in Granada and Jaén (Spain). Results: The present study reports on the adaptation of the DLI instrument within the Spanish context. Acceptably high values were obtained in the analysis of reliability and internal consistency, suggesting that this item can be reliably utilised for the exploration of the dynamics of internal functioning in secondary education and the evaluation of the distribution of leadership characteristics. Conclusions: The pilot study highlights how heads of studies and department heads are potential leaders, making it easier to set up and sustain educational projects in schools.